Kinetic modeling of hazelnut drying: Effects of different cultivars and drying parameters. (15th October 2017) - Giraudo, A.; Valentini, N.; Venturello, A.; Savorani, F.; Bertone, E.; Bonazzola, G.; Zeppa, G.; Geobaldo, F.
Abstract: In this study, for the first time, six different hazelnut cultivars, characterized by different carpological traits (diameter, volume, weight, density, shell thickness, shape index, empty volume between kernel and shell), were utilized for conducting 60 experiments in a lab‐scale convective dryer, in which different drying air conditions (temperatures: 20 °C, 35 °C, 50 °C; relative humidity: 20%, 40%, 60%; airflow: 0.5 m/s) were explored with a Design of Experiment approach. The obtained drying curves where mathematically modeled and, among the tested kinetic models, the Fick's equation proved to best fit the drying data and was chosen to estimate the equilibrium moisture content ( M e) and the drying rate ( k ) for each experiment, based on the studied variables. The k parameter was found to be greatly affected ( p  < .01) by the carpological traits related to the hazelnut dimension, by T and RH. Conversely, a weak correlation ( p ≈ .05) was found between the carpological traits and M e which, instead, resulted being greatly affected by T and RH ( p  < .01). Practical applications: The precise definition of the complex dynamics involved in hazelnut drying process represents a crucial step toward an exhaustive comprehension and optimization of the drying process itself. The possibility of tailoring the process parameters to guarantee the best drying conditions for a specific lot of shelled hazelnuts represents an important goal eagerly pursued by the modern confectionary industry. During the last years, this topic has attracted a broad industrial interest, resulting in many research studies investigating the drying process. Our study takes into consideration not only the classical drying parameters but also the variability introduced by the carpological traits of different hazelnut cultivars and allows defining a mathematical model of general applicability, which describes the drying process and that could be potentially exploited to optimize the performance of the hazelnut drying at the industrial level.